Bioactive potential of punicalagin: A comprehensive review - Irtiqa Shabir; Aamir Hussain Dar; Kshirod Kumar Dash; Sobiya Manzoor; Shivangi Srivastava; Vinay Kumar Pandey; Rafeeya Shams; Iqra Bashir; Shafat Ahmad Khan; Shaikh Ayaz Mukarram; Béla Kovács (Applied Food Research)
Pomegranates comprise bioactive components including polyphenols, tannins, and anthocyanins, which have demonstrated beneficial health effects. Pomegranates also act as a preventative measure for a variety of ailments, as per the promising results from human trials. Pomegranate juice consumption has shown promising outcomes in clinical trials against various diseases, including diabetes, prostate cancer, and cardiovascular disorders, and could be attributed to the punicalagin content of the juice. Punicalagin, a hydrolyzable tannin, is abundant in pomegranate juice and extracts. This review gives insight into the bioactive potential of punicalagin in the prevention of chronic ailments. The review includes the research conducted on punicalagin during 2010–2024. The origins of punicalagin, its method of action, and its therapeutic potential for diabetes, cardiovascular disease, cancer, neuroprotection, obesity, and respiratory illnesses are all discussed in this study. The antioxidant, anti-inflammatory, anti-cancer, and cardioprotective properties of punicalagin have been investigated. Punicalagin reduces inflammation by inhibiting multiple enzymes. Its potential to trigger cancer cell apoptosis may make it anti-cancer. Punicalagin reduces oxidative stress and improves endothelial function, enhancing cardiovascular health. Recent studies have shown that punicalagin has an excellent bioactive as well as therapeutic potential, and it has been suggested as a safe alternative for chemoprevention. As a natural substance, punicalagin shows potential for improving health in several ways. Its therapeutic potential and methods of action, however, need further investigation.